ILSA 2017 in Tromsø : proceedings from the 42nd annual conference of the International Lung Sound Association - Melbye, Hasse (Universitetet i Tromsø, 2017)
Edited by Hasse Medbye, med bidrag fra flere. In this conference there will be focus on all these determinants for efficient lung auscultation. In addition to free oral presentations, we have three symposia: on computerized analysis based on machine learning, on diagnostics, and on learning lung sounds, including the psychology of hearing. The symposia include extended presentations from invited speakers. The 42nd conference is the first in history arranged by a research unit for general practice. Primary care doctors are probably the group of health professionals that put the greatest emphasis on lung auscultation in their clinical work. Many patients with chest symptoms consult without a known diagnosis, and several studies have shown that general practitioners pay attention to crackles and wheezes when making decisions, for instance when antibiotics are prescribed to coughing patients. In hospital, the diagnosis of lung diseases is more strongly influenced by technologies such as radiography and blood gas analysis. Since lung auscultation holds a strong position in the work of primary care doctors, I think it is just timely, that the 42nd ILSA conference is hosted by General Practice Research Unit in Tromsø. I hope all participants will find presentations of importance, and that the stay in Tromsø will be enjoyable.